Imperfect magnetic field gradients in radial k‐space encoding—Quantification, correction, and parameter dependency. Issue 2 (27th September 2018) - Moussavi, Amir; Boretius, Susann
Abstract : Purpose: Sensitivity to imperfections of image‐encoding gradient fields may significantly impair widespread use of radial MR data acquisition. Such imperfections can cause individual echo shifts for each spoke acquired in the k‐space and may produce severe image artifacts. Therefore, fast and robust methods to quantify and correct for those echo shifts are required. Theory and Methods: Echo shifts can be induced by inhomogeneities of the static magnetic field (δnB ) and by imbalances of the imaging gradients (δnG ) mainly caused by eddy currents. However, mismatch between data acquisition and gradient switching may additionally play a role. From the position of the echo maxima of 2 opposing spokes, δnG and δnB can be determined and corrected by adapting the read‐dephasing gradient accordantly. This approach was implemented on MR‐systems of different field strengths, gradient systems, and vendors, and the dependencies of echo shift and acquisition parameters were analyzed. Data sets of phantoms and of mice under in vivo conditions were obtained using RF‐spoiled 2D radial‐FLASH. Results: The presented method allowed for echo‐shift detection and correction of < 1 data point, significantly improving the image quality in vitro and in vivo. Moreover, the method separated the effect of imbalanced gradients from those of magnetic inhomogeneities. The observed echo shifts were MR system‐specifically dependent on acquisition parameters such as gradient strengths and dwell time. Conclusions: By acquiring 12 spokes for a certain set of acquisition parameters, the proposed method successfully corrects echo shift‐related image artifacts independently of the MR system.